Impactos causados pela exótica invasora Megathyrsus maximus (Jacq.) B.K.Simon & S.W.L.Jacobs (Poaceae) sobre a vegetação da Mata Atlântica e sobre culturas agrícolas - Araújo, Kelianne Carolina Targino de (2023)
The introduction of exotic species has promoted the simplification of the native biota, in addition to causing several other negative effects on natural and anthropogenic ecosystems. The responsible process for causing this issue is called biological invasion (BI). Among the species responsible for promoting BI, there is the grass Megathyrsus maximus (Jacq.) B.K.Simon & S.W.L.Jacobs. In view of this, the present study aimed to evaluate the impacts caused by the exotic invasive on the autochthonous vegetation of the Atlantic Forest and on the germination of agricultural crops. For the impact assessment, 40 plots of 1m² were plotted, half of them installed in an invaded ares by Megathyrsus maximus (IA) and the other half in an aret without the presence of the species (NIA). Within these sample units, all individuals of herbaceous and semi-woody species were counted and statistical analyzes were carried out using these data (composition, richness, diversity and comparisons). In order to evaluate the effects of Megathyrsus maximus on the germination of agricultural crops, allelopathy tests were carried out. For this purpose, samples of the aerial part of the invasive exotic were collected and, after the usual procedures, the relevant analyzes were carried out (germinability, germination speed index, average germination time, coefficient of germination uniformity and comparisons). A total of 676 individuals distributed in 43 species in the IA and 943 individuals distributed in 90 species in the NIA were sampled. According to the analyses, the specific composition, taxonomic richness and diversity were affected by the presence of Megathyrsus maximus. The germination of agricultural crops Lactuca sativa (lettuce) and Solanum lycopersicum (tomato) were affected from the lower concentration of aqueous extracts (5%) of the invasive exotic, whereas Abelmoschus esculentus (okra) and Coriandrum sativum (coriander) were more tolerant to the allelochemical potentials, presenting a reduction in germination only in the highest concentrations of the extracts. The set of results presented indicate the need to create public policies aimed at controlling the Megathyrsus maximus species throughout the national territory, mainly in Conservation Units and productive areas.